Desenvolvimento e avaliação de meios filtrantes com nanofibras eletrofiadas e agentes bactericidas aplicados na filtração de ar - Bortolassi, Ana Cláudia Canalli (2019)
Filtration processes using fibrous filter media are very used to retain microparticles in a stream air due to its simple use, low operational cost and high collection efficiency. However, the study of submicron particles filtration is still incipient internationally and in Brazil, and also the application of nanofibers in this area. New technologies producing filter media are being developed to achieve high particles collection efficiencies with low pressure drop such as production of filters with nanofibers using the electrospinning process. The electrospinning method is very used among several techniques to produce nanofibers because it is simple and versatile. This method uses electrostatic force to obtain fibers with high contact surface area compared with those produced by other methods. Moreover, it is possible to add particles to the polymer solution using this method resulting in biocide filters. However, one of the difficulties to produce these filter media is the adjustment and control of several parameters which influence on production of the nanofiber as polymer concentration, type of solvent, nanofibers deposition time on the substrate, distance from the collector and electric tension. Therefore, the aim of this work was to develop filter media enable to remove particles in nanoscale and with bactericidal effect using the electrospinning technique. All of the filters of this study were produced using the polymer polyacrilonitrila (PAN) and characterized by Energy-dispersive X-ray spectroscopy (EDX), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), fiber diameter, thickness, porosity, permeability, pressure drop. The analyzes of EDX and XPS were evaluated just to filters with AgNO3, TiO2 and ZnO particles added to PAN solution. After these analysis, efficiency filtration, quality factor and bactericidal effect of filter media were evaluated. The experiments’ results from France showed filters with high efficiency filtration (≈100%), high quality factor (0.04 Pa-1) and bactericidal effect (≈100%) against initial E.coli concentration of 104 CFU/ml. The flow rate and duration of electrospinning relating to filtration efficiency and pressure drop of the filters produced in Brazil were evaluated. PAN2_90 filter reached the highest filtration efficiency (99,91% for diameters of particles of 100 nm) but the highest pressure drop (197,35 Pa-1). Filters developed in this work can be applied in air masks and air purification system, in other words, aiming to remove nanoparticles and bacteria from the environment.